Nesidiorchestes hawaiiensis Kirkaldy: new tribal assignment and lectotype designation (Hemiptera: Heteroptera: Miridae: Orthotylinae: Orthotylini) - Schwartz, Michael D.; Tatarnic, Nikolai (Zootaxa, 2008)
The preponderance of documented morphological evidence presented for Nesidiorchestes hawaiiensis Kirkaldy, 1902 argues for its tribal reassignment to the Orthotylini from the Halticini. A lectoype is designated for a male syntype maintained in the Natural History Museum, London.